Identification of surface-exposed linear B-cell epitopes of the nonfimbrial adhesin CS31A of Escherichia coli by using overlapping peptides and antipeptide antibodies. - Méchin, M C (1996)
As a first step toward the design of an epitope vaccine, by using the nonfimbrial adhesin CS31A of Escherichia coli as a carrier, a low-resolution topological and epitope map of the CS31A subunit was developed by using solid-phase peptide synthesis and polyclonal rabbit antibodies raised against both native and denatured proteins. Peptides constituting antigenic epitopes on the major subunit (ClpG) of the multimeric CS31A antigen were identified by examining the binding of the antibodies to 249 overlapping nonapeptides covering the amino acid sequence of ClpG. With antibodies raised against denatured ClpG subunit, seven major epitope regions, corresponding to residues 10 to 18, 45 to 58, 88 to 107, 148 to 172, 187 to 196, 212 to 219, and 235 to 241, were located. Most of the epitopes were hydrophilic and were located in variable regions, residing largely in loop regions at the boundaries of secondary structural elements of ClpG. In contrast, antibodies raised against native CS31A antigen reacted only with the peptide AVNPNA (positions 179 to 184), demonstrating that this peptide was the only linear B-cell epitope of the native protein. The different immunogenic profiles of native CS31A antigen and denatured ClpG indicated that the denaturation process resulted in marked conformational changes in the protein, which could expose epitopes hidden or absent in native CS31A. To identify the surface-exposed epitopes, nine peptides covering the dominant antigenic regions of ClpG were synthesized and used to prepare site-specific antibodies. Antipeptide antibodies were tested, in a competitive enzyme-linked immunosorbent assay (ELISA), for cross-reactivity with native CS31A and denatured ClpG subunit. Four of these antipeptide antibodies bound to the native protein in an accessibility ELISA, indicating that residues 44 to 56, 174 to 190, 185 to 199, and 235 to 249 were surface exposed on CS31A. These data indicate that an immunodominant surface-exposed linear epitope was present in the region from positions 179 to 184 of ClpG in the native CS31A antigen on intact bacterial cells and suggest that the four surface-exposed epitopes constitute potential sites for insertions or substitutions with heterologous peptides.